[PP.35.34]: RISK OF DIURETIC INDUCED HYPONATREMIA IN PATIENTS WITH HYPERTENSION. (June 2015) - Cristescu>, C.>; Homentcovschi, C.; Daneasa, A.; Anton, M.; Ianula, R.
Abstract : Objective: To determine susceptibility to diuretic induced hyponatremia in groups of age and sex Design and method: According to many previous studies, hyponatremia is a common cause of morbidity in different age groups. In geriatric patient hyponatremia has been associated in many studies with fracture occurrence due to falls, unsteadiness and attention deficits. As the new guidelines for the management of hypertension still recommend diuretics as first line treatment for specific categories of patients, we designed a retrospective monocentric 1 year follow up study to determine susceptibility to diuretic induced hyponatremia in groups of age and sex. 143 patients were enrolled in this study. 91 of these presented serum sodium levels between 112 and 134.9 and were considered eligible for our purpose. We divided the eligible patients in two main groups, young and elder, considering as elder criteria age > 75 years old (WHO – ambiguous definition of old patient). Further, for each of these two groups, other two groups were generated according to sex. We tested all our groups for mild (130–134.5 mmol/l), moderate (125–129.9 mmol/l) and severe (<125 mmol/l) hyponatremia. All data were processed using Microsot Office Excel 2010. Results: More than 50 percent of patients in both groups developed mild hyponatremia with an increased value for the younger group after one year of diuretic treatment (72% vs 65%; p = 0.01). On the other hand, although few patients developed moderate and severe hyponatremia the elder group was more susceptible (35% for > 75 yr vs 28% for < 75 yr). No matter the severity of hyponatremia women were more affected than man. Conclusions: The use of diuretics, especially thiazide, remains a strong indication for the management of hypertension. Our study proves that in these conditions, an increased number of patients develop hyponatremia and that old people are more susceptible to severe and moderate values. This is why we consider that a very careful screening for hyponatremia should be performed in all patients following treatment with diuretics, and that this screening should be mandatory in women and old patients.